Snack Business Popcorn With Various Flavors - Rizki Alamsyah; Dessy Aliandrina (ConCEPt - Conference on Community Engagement Project, 2023)
Based on the results of observations made by researchers, Popcorn is generally still rarely found, especially in the Batam city area, where most UMKM or street vendors prefer to sell fried snacks and the like. Foods or snacks that contain a lot of oil are not very good for health. This research focuses on the snack food business that sells various flavors of popcorn. The name of this business is Corzen Popcorn. The presence of Corzen Popcorn is to have a good impact on people who really like light food but are free from oily food. Sales in this business are carried out through social media, namely Instagram and Facebook. Operational activities carried out by Corzen Popcorn are producing and selling products from Corzen Popcorn, namely popcorn with various flavors.